On the subordination of the policy of the Russian Empire to a Western colonial campaign in the Balkans in the 19th century - Šuljagić Sanja (Srpska Politička Misao)
In this paper, the subject of research is the cause of insufficient support of the Russian Empire to Serbian and other Balkan insurgents during the establishment of the modern geopolitical constellation in the Balkan Peninsula in the nineteenth century. The objective of the research is to prove that the cause of the insufficient support of the Russian Empire to the Balkan insurgents in that period was the ideological and geopolitical subordination of the foreign policy of the Russian Empire to the Western colonial campaign on the Balkan Peninsula in the same period. By applying analytical-synthetic and comparative methods, it is shown that the ideological and geopolitical subordination of the policy of the Russian Empire to Western political and economic interests became noticeable in the period after the Russian Empire had begun to represent an obstacle to commercial aspirations of European trading companies towards India and the Far East. From that time onwards, anti-Russian propaganda began in England and European states, and later also military and non-military campaigns by representatives of European states against the Russian Empire. As a consequence of the Western agenda of "penetration to the East," in 1815, after the Congress of Vienna, the influence of the Russian Empire on the geopolitical constellation of the Balkan Peninsula was overshadowed by European political interests.